El capital intelectual de las cajas de ahorros españolas - Rodríguez Ruiz, Óscar (Cuadernos de Estudios Empresariales, 2006)
Spanish Savings Banks have experienced a notorious organic growth in the last years. Furthermore they have increased countinously their market share. Financial magnitudes explain partially this trend, but it really has to do with the set of intangible assets that compose the intellectual capital of these institutions. The aim of this paper is to offer scientific evidences of the intellectual capital of Spanish Savings Banks. The qualitative technique of in depth interview and the questionnaire quantitative technique are used as empiric tools.